SIGNIFICANCE CONSTRUCTION IN AN OFFICIAL SPEECH (SAN VITO, 1982) - Rimolo Bariatti, Annamaria (2014)
The aim of this essay is to explore the possibility of significance construction in the speechgiven by the Agronomical Engineer Claudio Antonio Volio Guardia, former Costa RicanMinister of Agriculture (1949-1953) on February 28, 1982 in accordance to the discourseanalysis after Teun A. van Dijk. In order to achieve this goal we explored his most relevantconcepts (action, context, power and ideology) trying to establish the connection betweendiscourse and society within our modernity.